Various Approaches to the Synthesis of Magnetic Nanoparticles - Chapa, Christian (CRC Press, Taylor & Francis Group, 2024)
This chapter offers a comprehensive exploration of magnetic nanoparticles, covering their introduction and the intricacies of magnetism at the nanoscale. It explores the superparamagnetism phenomena and gives a summary of the various biomedical uses for magnetic nanoparticles. The main goal is a thorough examination of synthetic methods for producing magnetic nanoparticles. Physical techniques like gas-phase synthesis, laser-induced pyrolysis, and high-energy ball milling, as well as chemical techniques including chemical coprecipitation, sol-gel, and solution combustion are examined. The chapter ends with some insightful observations that will be helpful to both researchers and practitioners in the subject.